Firearm Injury Prevention and Extreme Risk Protection Orders. Issue 3 (5th May 2022) - Wortzel, Hal S.; Simonetti, Joseph A.; Ryan, Arthur T.; Matarazzo, Bridget B.
Abstract : Extreme risk protection orders (ERPOs) represent a potential mechanism to facilitate firearm-related lethal means safety. ERPOs are a legal mechanism that enables law enforcement to temporarily remove firearms from, and prevent firearm purchase by, an individual who presents a significant danger to self or others, as determined by a court of law. While few jurisdictions currently allow mental health professionals to initiate ERPO petitions, it nonetheless seems important that clinicians be familiar with ERPOs, as clinicians may still serve an important role in disseminating information and facilitating judicious petitions. However, ERPO laws remain quite new, and the implications for mental health professionals when participating (directly or indirectly) in ERPOs remain unclear. This column introduces readers to ERPOs and offers resources to learn more about how ERPOs work across various jurisdictions.